How does trade sale privatization work? Evidence from the fixed-line telecommunications sector in developing countries - Theodora Welch; Rick Molz (Fondazione Eni Enrico Mattei (FEEM), 2002)
This research examines the effects of privatization transaction strategy on enterprise performance in developing economies. Focusing on trade sale privatization, we use an event-driven data strategy and time-series regression techniques on data covering fixed-line telecommunications operators between 1980 and 1998. The results show performance benefits are realized when privatization trade sales introduce large-block foreign shareholdings and hybrid forms of governance, such as joint ventures or consortia. These hybrid governance structures capture more complex ownership effects during privatization restructuring, particularly when compared with the dispersed shareholdings of share issue privatization, which show no discernable effect on performance. We argue traditional financial models are too focused on large-scale market-driven mechanisms at the expense of institution-building mechanisms, and as such fail to capture important contributors to performance improvement. We advance a comparative institutional lens to better understand how "firms effects" matter for privatization restructuring and performance.
Keywords: 330; Privatisierung; Eigentümerstruktur; Direktinvestition; Telekommunikationssektor; Entwicklungsländer